Ascent and decompressional boiling of geothermal liquids tracked by solute mass balances: a key to understand the hydrothermal explosions of Milos (Greece) - Chiodini, G.; Bini, G.; Massaro, S.; Caliro, S.; Kanellopoulos, C.; Tassi, F.; Vaselli, O.; Vougioukalakis, G.; Bachmann, O. (Frontiers in Earth Science, 2023)
Hydrothermal explosions occur through the sudden expansion of fluids at or near boiling condition with little or no precursors, making difficult any kind of predictions. Here, we investigate the processes occurring within hydrothermal systems in a potential critical state for explosions through a new methodology based on mass balances of thermal water solutes. The usage of this method reveals that the pore water samples of the Paleochori Bay (Milos, Greece; < 20 m depth b.s.l.), chosen as a case study, are binary mixtures of a geothermal component and seawater, from which steam is either added through condensation of underlying, ascending vapors or separates through boiling. This new method enables us to quantify and map both the fraction of the original geothermal liquid in each pore water sample and that of the vapor supplied or separated from the solutions. Furthermore, the method allows us to compute the composition of the geothermal endmember. The map of the fraction of supplied vapor shows that decompressional boiling of ascending liquids predominantly focuses in the central part of the Paleochori Bay. Both the estimated composition and temperature (324 °C) of the geothermal liquid endmember overlap those measured in geothermal well fluids at or near-boiling condition, except SO 4 and SiO 2 . The lower SiO 2 and higher SO 4 content in the pore waters may be ascribed to the current production of an impermeable cap, which enables underlying fluids to accumulate and pressure to buildup. The evidence of liquid at or near boiling conditions and self-sealing processes in the Paleochori Bay suggests that decompressional boiling during abrupt pressure drawdowns might have caused hydrothermal explosions at Milos in historical times, whose occurrence is testified by several hydrothermal craters. Finally, our work shows that similar conditions favoring explosions still affect the hydrothermal system of Milos.